If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + (x + -3) + -1(x + -3) = 5 + -1(3 + -1x) Reorder the terms: 7 + (-3 + x) + -1(x + -3) = 5 + -1(3 + -1x) Remove parenthesis around (-3 + x) 7 + -3 + x + -1(x + -3) = 5 + -1(3 + -1x) Reorder the terms: 7 + -3 + x + -1(-3 + x) = 5 + -1(3 + -1x) 7 + -3 + x + (-3 * -1 + x * -1) = 5 + -1(3 + -1x) 7 + -3 + x + (3 + -1x) = 5 + -1(3 + -1x) Reorder the terms: 7 + -3 + 3 + x + -1x = 5 + -1(3 + -1x) Combine like terms: 7 + -3 = 4 4 + 3 + x + -1x = 5 + -1(3 + -1x) Combine like terms: 4 + 3 = 7 7 + x + -1x = 5 + -1(3 + -1x) Combine like terms: x + -1x = 0 7 + 0 = 5 + -1(3 + -1x) 7 = 5 + -1(3 + -1x) 7 = 5 + (3 * -1 + -1x * -1) 7 = 5 + (-3 + 1x) Combine like terms: 5 + -3 = 2 7 = 2 + 1x Solving 7 = 2 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + -1x = 2 + 1x + -1x Combine like terms: 1x + -1x = 0 7 + -1x = 2 + 0 7 + -1x = 2 Add '-7' to each side of the equation. 7 + -7 + -1x = 2 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 2 + -7 -1x = 2 + -7 Combine like terms: 2 + -7 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5
| 2(x+10)+2x=168 | | p(x)=x^2+2xfindp(1) | | 3xsquare-243=0 | | 4x-10=-20 | | 3(2c+d)-2d= | | 4*e^5x+1=9 | | (7-3x)(2x-6)=-42 | | x^3-21x-90=0 | | (y/4)-3=y/3 | | x^3-21x-90= | | (3x-2)(3x-2)=20 | | y=-0.0980392156863x+15.0196078431 | | x-21x-90=0 | | 3(2x-1)=3x+6 | | x(12-2x)(10-2x)=0 | | y/4-3=y/3 | | 3n+2=-40 | | -3-20=-x+10 | | x+y=365 | | 6x+4=9x-17 | | 10x-3y+3x-4y=0 | | 3x-2=-47 | | 21(w-937)=630 | | 0=8+4x | | 7x-11=x+1 | | -47+5x=30-2x | | k-10/2=5 | | w-650=500000 | | 2.33*x=9 | | 4.8+v=14 | | (4z-7)(6+z)=0 | | x(32-6x)=0 |